2016
DOI: 10.4103/0970-9290.199588
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of indirect pulp capping using three different materials: A randomized control trial using cone-beam computed tomography

Abstract: Success rate for IPC was 96.85%. A significant difference was obtained in the average thickness of reparative dentin at immediate postoperative and 6-month postoperative values in all three groups suggesting distinct barrier formation. Similar significant findings were obtained in radiodensity of barrier formed (in HU). All three materials were found to be equally suitable as IPC agents suggesting mineral gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 0 publications
2
40
1
1
Order By: Relevance
“…Furthermore, there was a decrease in bacterial counts for teeth treated with CH cement and an inert material (wax or gutta-percha) (Pinto et al 2006, Bressani et al 2013. The thickness of the reparative dentine formed was also similar between teeth treated with a CH cement, or GIC (Mathur et al 2016).…”
Section: Descriptive Analysismentioning
confidence: 62%
See 1 more Smart Citation
“…Furthermore, there was a decrease in bacterial counts for teeth treated with CH cement and an inert material (wax or gutta-percha) (Pinto et al 2006, Bressani et al 2013. The thickness of the reparative dentine formed was also similar between teeth treated with a CH cement, or GIC (Mathur et al 2016).…”
Section: Descriptive Analysismentioning
confidence: 62%
“…The thickness of the reparative dentine formed was also similar between teeth treated with a CH cement, or GIC (Mathur et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…Two randomized clinical trials (Mathur et al . , Menon et al . ) reported successful clinical (no pain, absence of sinus tract) and radiographic (no sign of external and internal resorption, presence of calcified bridge) outcomes following the use of MTA and TheraCal LC when used for indirect pulp capping in primary teeth.…”
Section: Vital Pulp Therapiesmentioning
confidence: 97%
“…The authors also reported that exposing cone‐beam computed tomography images in children was difficult because they tended to move during the long exposure time (Mathur et al . ).…”
Section: Vital Pulp Therapiesmentioning
confidence: 97%
“…All studies were performed in secondary care by a single research team, which limits the external validity of the results. Furthermore, studies 6,10,30 published so far comparing other materials, such as mineral trioxide aggregate or calcium silicate, were not included in this review because they did not fulfill the selection criteria. Therefore, there is a need for further well-designed and well-reported randomized controlled clinical investigations assessing other relevant outcomes for longevity of restorations after indirect pulp treatment.…”
Section: Discussionmentioning
confidence: 99%